2004
DOI: 10.1118/1.1774131
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: A novel boundary condition using contact elements for finite element based deformable image registration

Abstract: Deformable image registration is an important tool for image-guided radiotherapy. Physics-modelbased deformable image registration using finite element analysis is one of the methods currently being investigated. The calculation accuracy of finite element analysis is dependent on given boundary conditions, which are usually based on the surface matching of the organ in two images. Such a surface matching, however, is hard to obtain from medical images. In this study, we developed a new boundary condition to ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 16 publications
1
56
0
Order By: Relevance
“…In an extension of this work, Didier et al 39 used the same FEM model and investigated the kinematic effects of the ribs on the motion during a breathing cycle by using a finite helical axis ͑FHA͒ method. Extending the work of Zhang et al, 37 Werner et al 34,45 recently proposed a respiratory lung motion model incorporating contact mechanics. Instead of using contact elements, an augmented Lagrangian algorithm was used for the contact formulation in the FEM software COMSOL MULTIPHYSICS ͑COMSOL AB, Sweden͒.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In an extension of this work, Didier et al 39 used the same FEM model and investigated the kinematic effects of the ribs on the motion during a breathing cycle by using a finite helical axis ͑FHA͒ method. Extending the work of Zhang et al, 37 Werner et al 34,45 recently proposed a respiratory lung motion model incorporating contact mechanics. Instead of using contact elements, an augmented Lagrangian algorithm was used for the contact formulation in the FEM software COMSOL MULTIPHYSICS ͑COMSOL AB, Sweden͒.…”
Section: Introductionmentioning
confidence: 99%
“…35 Finite-element lung models have also been used to evaluate the effect of gravity on respiratory physiology 36 and to find surface matching of organs in two images in deformable image registration techniques. [37][38][39][40] Recently, finite-element lung models for tumor tracking at the end of inhalation incorporating contact conditions have been proposed. 35,34 In FEM, the effectiveness of the model and its accuracy in predicting tumor motion depend on several important issues including the quality of the patient geometric model and the regularity and accuracy of the finite-element mesh.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several parameters for lung tissue elasticity and poroelasticity have been proposed [34,5,35,10,36], although there is no consensus in the values in the literature. In this study, we have chosen parameters as shown in Table 1 …”
Section: Simulation Parametersmentioning
confidence: 99%